2005
DOI: 10.1103/physreve.71.037103
|View full text |Cite
|
Sign up to set email alerts
|

Spatial prisoner’s dilemma game with volunteering in Newman-Watts small-world networks

Abstract: A modified spatial prisoner's dilemma game with voluntary participation in Newman-Watts small-world networks is studied. Some reasonable ingredients are introduced to the game evolutionary dynamics: each agent in the network is a pure strategist and can only take one of three strategies (cooperator, defector, and loner); its strategical transformation is associated with both the number of strategical states and the magnitude of average profits, which are adopted and acquired by its coplayers in the previous ro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
63
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 177 publications
(67 citation statements)
references
References 26 publications
2
63
0
Order By: Relevance
“…For imitation type dynamical rules [3,4] the multiagent voluntary prisoner's dilemma on a square lattice exhibited a self-organizing pattern with rotating spiral arms [22,25,26]. In well-mixed populations [21,27] and also on some small-world networks [28][29][30] this interaction yielded global oscillations in the strategy frequencies. The "tragedy of the commons" is avoided in all these systems because the cyclic component supports the survival of all three strategies.…”
Section: Example: Voluntary Prisoner's Dilemmamentioning
confidence: 99%
“…For imitation type dynamical rules [3,4] the multiagent voluntary prisoner's dilemma on a square lattice exhibited a self-organizing pattern with rotating spiral arms [22,25,26]. In well-mixed populations [21,27] and also on some small-world networks [28][29][30] this interaction yielded global oscillations in the strategy frequencies. The "tragedy of the commons" is avoided in all these systems because the cyclic component supports the survival of all three strategies.…”
Section: Example: Voluntary Prisoner's Dilemmamentioning
confidence: 99%
“…Similar results were reported by Aktipis (2004) who considered the effect of contingent movement of cooperators: the players walked away once a defection occurred in the previous step. In some sense, this "win-stay, lose-move" strategy is analogous to voluntary participation which also enhance cooperation (Saijo and Yamato, 1999;Hauert et al, 2002;Szabó and Hauert, 2002a;Wu et al, 2005a) as detailed in the subsequent section.…”
Section: Prisoner's Dilemma On Evolving Networkmentioning
confidence: 99%
“…Mathematicians, biologists, and physicists alike have found the phenomena of emergence of cooperative behavior fascinating. Since the ground-breaking work on repeated or iterated games based on the Prisoner's Dilemma (PD) game by Axelrod [1,2], there has been a continuous effort on exploring the determining factors on possible cooperative behavior in evolutionary games based on the PD game and its variations [3,4,5,6,7,8], with a recent emphasis on the effects of spatial structures such as regular lattices [5,6,9,10,11] and networks [8,12,13,14,15,16,17]. Remarkably, it was found that cooperation can be induced in a repeated PD game by cleverly designed strategies.…”
Section: Introductionmentioning
confidence: 99%